Development administration: temporal and spatial dimensions - Bagai, Anita (2009)
Development administration is a complex phenomenon which has to be understood in a broader perspective of social change. It came to be known as an action-oriented, goal oriented system with capacity to transform societies from backwardness to modernity. Developing countries must essentially opt for indigenous models of development instead of following the standard prescriptions of the West. Scholars have underscored importance of understanding the temporal and spatial dimensions of development administration. Besides the social, economic, political, the cultural and organisational contexts, the temporal and spatial dimensions occupy an important place. This article attempts to examine the significance temporal characteristics of developed countries and the differences between developed and developing countries as far as temporal characteristics are concerned. - Reproduced.
Keywords: Development administration